The Effect of Product Quality, Business Capital, and Digital Marketing on MSME Development in Indonesia - Erni Puji Astutik; Lorentino Togar Laut (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Micro, small, and medium enterprises in Magelang Regency face challenges in maintaining competitiveness due to limited access to quality raw materials, capital, and effective marketing strategies. Digital tools, such as social media and digital payments, have transformed consumer behavior, offering opportunities for business growth. This study aims to evaluate the impact of product quality, business capital, and digital-based marketing on the development of micro, small, and medium enterprises in Magelang Regency. A quantitative approach was used, with data collected from 40 enterprises through questionnaires and analyzed using multiple linear regression. The findings show that digital-based marketing significantly enhances enterprise development, particularly in increasing sales turnover and customer growth. In contrast, product quality and business capital have no significant impact, likely due to local market preferences for affordable products and the use of capital for daily operations. These results suggest that digital marketing is a key driver of growth for micro, small, and medium enterprises in Magelang Regency. The study concludes that enterprise owners should prioritize digital marketing strategies, such as using social media and e-commerce platforms, to boost competitiveness, while policymakers should support digital literacy programs to strengthen the local economy.